Critical Oscillation Constant for Difference Equations with Almost Periodic Coefficients. (14th October 2012) - Hasil, Petr; Veselý, Michal
Abstract : We investigate a type of the Sturm-Liouville difference equations with almost periodic coefficients. We prove that there exists a constant, which is the borderline between the oscillation and the nonoscillation of these equations. We compute this oscillation constant explicitly. If the almost periodic coefficients are replaced by constants, our result reduces to the well-known result about the discrete Euler equation.